American Presidential Candidate Spouses - Elder, Laurel. author. aut Link
XV, 158 p. 16 illus.
Keywords: The book offers a comprehensive analysis of public opinion toward presidential candidate spouses over the course of three decades, drawing on multiple theoretical frameworks including the concept of “new traditionalism” and a plethora of empirical data to explore why some spouses engender greater support than others—and what these reactions reveal about the American public and the gendered nature of the American presidency. Recognizing that presidential candidate spouses are important but understudied political actors, this book provides extensive analysis of public evaluations of Bill Clinton and Melania Trump during the 2016 presidential election as well as the presidential candidate spouses in the 1992 and 2012 elections and places public reaction to these individuals in historical context. The book considers important trends in U.S. elections including party polarization from the distinctive vantage points of candidate spouses and explores the symbolic importance of historic firsts including the first African American candidate spouse and the first male candidate spouse. No other work provides a systematic exploration of public opinion towards candidate spouses as distinct political entities across the modern political era. .